Upaya Peningkatan Kemampuan Guru Dalam Evaluasi Hasil Belajar Melalui Lokakarya Berkesinambungan Di SMPN 56 - Naryo, Naryo (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2023)
This research is motivated by the existence of various problems related to the teacher's ability to prepare test questions for student learning outcomes that have not referred to established standards. Collecting data using the method of observation, documentation, and interviews. The analysis is carried out through records of changes that occur in the stages of implementing the action until saturated data is found, then it is concluded as a whole. The results of this study indicate that the implementation of continuous workshops has a significant impact on improving the skills of SMP Negeri 56 Jakarta teachers. This can be seen from the ability to write quality questions in each cycle has increased. The ability to write multiple choice questions in the pre-action obtained an average of 61.06% and in cycle 1 increased to 70.72% because it did not meet the performance indicators, the action was continued in cycle 2 and the average acquisition increased to 79.41% and already fulfilled the performance indicators in this study . Furthermore, the ability to write description questions in the pre-action obtained an average of 60.54% and in cycle 1 increased to 70.56% because it did not meet the performance indicators, the action was continued in cycle 2 and the average acquisition increased to 80.95% and already fulfilled the performance indicators in this study.